2017
DOI: 10.3389/fphar.2017.00550
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Spatial Memory Recognition Due to Cognitive Style

Abstract: Field independence refers to the ability to perceive details from the surrounding context as a whole and to represent the environment by relying on an internal reference frame. Conversely, field dependence individuals tend to focus their attention on single environmental features analysing them individually. This cognitive style affects several visuo-spatial abilities including spatial memory. This study assesses both the effect of field independence and field dependence on performance displayed on virtual env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 44 publications
1
17
0
1
Order By: Relevance
“…Generally, the positive effect of OC has not been systematically found for visuo-spatial cognition, and, when evidenced, it seems to be related to the type of OC used [ 13 16 ]. To the best of our knowledge, no studies have attempted to assess the effect of OC on topographic memory, despite findings demonstrating it to be sensitive to gender-related effects and hormonal fluctuations [ 2 , 17 29 ]. Due to the expected effect of OC on memory, and due to the presence of gender-related effects on topographic memory, this type of memory could be a target of OC effects.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the positive effect of OC has not been systematically found for visuo-spatial cognition, and, when evidenced, it seems to be related to the type of OC used [ 13 16 ]. To the best of our knowledge, no studies have attempted to assess the effect of OC on topographic memory, despite findings demonstrating it to be sensitive to gender-related effects and hormonal fluctuations [ 2 , 17 29 ]. Due to the expected effect of OC on memory, and due to the presence of gender-related effects on topographic memory, this type of memory could be a target of OC effects.…”
Section: Introductionmentioning
confidence: 99%
“…Those studies did not examine students'critical thinking based on cognitive style. In fact, cognitive style may be an key factor in determine students's existing knowledge and learning performance (Chinien & Boutin, 1993;Mayer & Massa, 2003;Riding, & Sadler-Smith, 1997;Sadler-Smith, & Badger, 1998;Sadler-Smith & Riding, 1999;Tascón, Boccia, Piccardi, & Cimadevilla, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive style influences spatial memory potentially. For example, a study showed that participants who were better at perceiving the environment as a whole outperformed participants who focused their attention on single environmental features in an object location memory task [43]. Another possibility is that the difference in high and low visual realism may be too subtle.…”
Section: Discussionmentioning
confidence: 99%